Evaluation of the modified-ceylon copra kiln for accelerated production of ball copra - Marikkar, Mohammed Nazrim; M.K.I. , Banu,; C, Yalegama (Universiti Putra Malaysia, 2009)
Finding a way to expedite the formation of ball copra would be advantageous to sustain a steady supply. This study attempted to investigate the effect of kiln drying on the rate of formation of ball copra. Three samples containing fifty partially dried-coconuts were placed as a single layer in three compartmentalized blocks namely, Front: Blok-1, Middle: Block-2, and Rear: Block-3 in the copra bed of the modified-Ceylon copra kiln. From each of the three blocks, thirty coconuts were selected randomly for labeling and their fresh weights were recorded. The samples were subjected to intermittent drying in the kiln by thirty five firing cycles using charcoal dust as the fuel source. The temperature distribution pattern of the three blocks during the first six firing was monitored at three hourly intervals. The weight losses of individual coconuts in each block were measured after the completion of each firing. The results showed that, there was a significant (p<0.05) effect of copra bed temperature on the weight losses of the samples. The first ever ball copra formation was detected in the Block-3 after the completion of the 12th firing. The percentages of ball copra formed at the end of 35th firing were 44%, 78%, and 94%, in Block-1, Block-2, and Block-3, respectively. Analytical studies indicated that the quality indices of ball copra were comparable to those of the edible white copra.